Faktor faktor yang mempengaruhi kemiskinan di kabupaten kutai kartanegara - Aziz, Gamal Abdul; Rochaida, Eny; Warsilan, Warsilan (INOVASI, 2016)
One of the main indicators of the success of national development is decreasing the rate of number of poor people. This means that one of the main criteria of the leading sectors of national development is the effectiveness in decreasing the number of poor people . Both central and local government has tought to implement policies and programs to reduce poverty, but still far from the main issue. For Kutai Kartanegara Regency, poverty is a strategic issue and get top priority to be solved. Poverty itself is an issue that involves many aspects because it is associated with low income, illiteracy, poor health status and inequality between the sexes as well as poor environmental. Poverty is one of the socio- economic benchmarks in assessing the success of the government's development in an area. There are so many social problems that are negatively arise due to increasing poverty. Poverty in Kutai has decreased from previous years, but poverty in Kutai to 2008 shows quite high number, its reaching 18.99 percent The purpose of this study was to: Analyze and test the effect of economic growth, education, unemployment and government expenditure on programs countermeasures poverty through the provision of capital to the Business Group (KUBE) in Kutai Kartanegara Regency. Analyze and examine the variables are the dominant influence on poverty in Kutai. Based on the pattern of the relationship, this study attempts to explain the causal relationship between several variables. In this study will explain the causal relationship between variables per capita income, education , unemployment and Financing KUBE. Based on its design, this study is a research analysis of secondary data documentation. This study suggests that the per capita income, education , unemployment and financing KUBE affect the level of poverty in Kutai regency. Although per capita income, education and KUBE no significant influence but was able to reduce poverty and unemployment variables greatly affect the increasing number of poor people .Keyword: Poverty , Education , Economic Growth , Unemployment and Government Expenditure